Sodium bismuth titanate-based lead-free pyroelectric ceramic material with bismuth layered structure and preparation method of sodium bismuth titanate-based lead-free pyroelectric ceramic material
By doping Li and Ce elements into the bismuth-layered sodium titanate-based lead-free pyroelectric ceramic materials with bismuth layered structure, the problem that existing materials are difficult to have both high Curie temperature and high pyroelectric coefficients is solved, and efficient pyroelectric performance and stable device performance are achieved, which is suitable for miniaturization and integrated development.
Patent Information
- Application Number
- CN202411857581.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing lead-free pyroelectric materials are difficult to have both high Curie temperature and high pyroelectric coefficients, and lead-containing materials have environmental protection problems, which limits the development of devices miniaturization and integration.
Using a bismuth sodium titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure, the chemical formula of Na0.5Bi4.5-x(Li1/3Ce2/3)xTi4O15 is formed to increase the Curie temperature and pyroelectric coefficient of the material by doping Li and Ce elements at the A-position of the bismuth sodium titanate to replace part of the Bi elements.
The combination of high Curie temperature and high pyroelectric coefficient is achieved, ensuring that the material does not depolarize in the high temperature environment of reflow soldering, and is suitable for surface-mount packaging technology, which promotes the miniaturization and integration of devices.
Smart Images

Figure CN119683994A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of pyroelectric infrared detection materials, and more specifically, relates to a sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure and a preparation method thereof. Background Art
[0002] Infrared photoelectric detection technology is widely used in military, industrial, life and other fields. Among them, uncooled pyroelectric infrared has gradually become a research hotspot due to its advantages such as low power consumption, small size and low cost.
[0003] Pyroelectric ceramic materials are usually used as the core sensitive element of uncooled infrared detectors. They can generate electrical responses when the temperature changes. They have the characteristics of low cost, high sensitivity and easy preparation. The detection ability of these uncooled pyroelectric infrared detectors mainly depends on the performance of pyroelectric ceramics, which is mainly reflected in the pyroelectric coefficient (p) and Curie temperature (T c ) are two key parameters. The pyroelectric coefficient is determined by the polarization change caused by temperature change, reflecting the material's ability to convert temperature fluctuations into electrical signals; while a higher Curie temperature ensures the working and processing temperature range of the pyroelectric material.
[0004] The most widely used pyroelectric material at present is lead zirconate titanate ceramic (PZT). However, the Curie temperature of PZT (230°C) is lower than the temperature of the reflow soldering process (260°C). The high temperature environment of reflow soldering will cause PZT to depolarize, which will lead to device failure. Therefore, it is limited to the use of surface mount packaging technology, which makes it difficult to meet the development needs of device miniaturization and integration. In addition, the use of lead-containing materials also causes problems that conflict with hazardous substance regulations.
[0005] At present, the main lead-free pyroelectric materials are Bi 0.5 Na 0.5 TiO3(BNT) based, BaTiO3(BT) based and K 0.5 Na 0.5 NbO3(KNN) based, among which BNT based and BT based can improve their pyroelectric coefficient by doping, but at the cost of greatly reducing the Curie temperature, it is difficult to maintain their performance under 200℃. Therefore, the development of lead-free materials with high Curie temperature as a substitute for lead-based ceramics is crucial to promote the development of environmentally friendly electronic devices. Summary of the invention
[0006] In view of the above defects or improvement needs of the prior art, the present invention provides a sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure and a preparation method thereof. The base material of the pyroelectric ceramic material is a sodium bismuth titanate-based bismuth layered structure with a high Curie temperature, and Li and Ce elements are doped at the A position of the sodium bismuth titanate-based material to replace part of the Bi element, thereby solving the technical problem in the prior art that it is difficult to simultaneously achieve both a high Curie temperature and a high pyroelectric coefficient.
[0007] To achieve the above object, according to one aspect of the present invention, a sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure is provided. The chemical formula of the pyroelectric ceramic material is Na 0.5 Bi 4.5-x (Li 1 / 3 Ce 2 / 3 ) x Ti4O 15 , where the value of x is greater than 0 and less than or equal to 0.2.
[0008] As a preferred embodiment of the present invention, the value of x is 0.025 to 0.1.
[0009] As a preferred embodiment of the present invention, the pyroelectric ceramic material has a relative dielectric constant of 100 to 150 and a dielectric loss of less than or equal to 0.006 under the test conditions of 25° C. and 1 kHz.
[0010] As a preferred embodiment of the present invention, the Curie temperature of the pyroelectric ceramic material is higher than 600°C; and the pyroelectric coefficient is 70-150 μCm at 25°C. 2 K -1 The current response merit factor of pyroelectric is (0.3~0.6)×10 -10 m V -1 , voltage response merit factor is 0.02~0.05m 2 C -1 , the detectivity merit factor is (1.6~4)×10 -5 Pa -1 / 2 .
[0011] According to another aspect of the present invention, a method for preparing a sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure is provided, the method comprising the following steps:
[0012] (1) According to Na 0.5 Bi 4.5-x (Li 1 / 3 Ce 2 / 3 ) x Ti4O 15 According to the stoichiometric ratio, Na2CO3, Bi2O3, Li2CO3, CeO2 and TiO2 are weighed and mixed, ball milled once, and dried to obtain a mixed powder;
[0013] (2) pre-sintering the mixed powder, performing secondary ball milling, drying, adding a binder and then granulating, molding, demolding and sintering to obtain a ceramic sheet;
[0014] (3) coating both sides of the ceramic sheet with silver paste, sintering and shaping, placing the ceramic sheet in silicone oil for pressure polarization, and obtaining the sodium bismuth titanate-based lead-free pyroelectric ceramic material with the bismuth layered structure.
[0015] As a preferred embodiment of the present invention, the conditions of the first ball milling and the second ball milling are the same, specifically: using anhydrous ethanol as the solvent, setting the ball milling speed to 200-400 r / min, and ball milling for 6-24 hours.
[0016] As a preferred embodiment of the present invention, the pre-firing conditions are to heat up to 600-900°C at 3-5°C / min and keep warm for 1-5h; the plastic removal conditions are to heat up to 500-650°C at 0.5-2°C / min and keep warm for 1-5h; the sintering conditions are to heat up to 900-1200°C at 1-5°C / min and keep warm for 1-5h.
[0017] As a preferred embodiment of the present invention, the sintering and shaping conditions are to keep the temperature at 500-700° C. for 10-30 minutes.
[0018] As a preferred embodiment of the present invention, the method further comprises: after the bismuth layered structure sodium bismuth titanate-based lead-free pyroelectric ceramic material is obtained, heat treating it, specifically: placing the polarized bismuth layered structure sodium bismuth titanate-based lead-free pyroelectric ceramic material in an annealing furnace at 300°C, keeping it warm for 5 to 15 minutes, and then taking it out and cooling it naturally.
[0019] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0020] (1) The pyroelectric ceramic material of the present invention uses a sodium bismuth titanate matrix with a bismuth layered structure having a high Curie temperature (Curie temperature is 660°C, and the general formula is (Bi2O2) 2+ (A n-1 B n O 3n+3 ) 2- ), and doping Li and Ce elements at the A position of the sodium bismuth titanate base of the bismuth layered structure to replace part of the Bi element, in addition, following the principle of charge conservation, 1 / 3 mole of Li and 2 / 3 mole of Ce are selected to replace 1 mole of Bi, and the obtained pyroelectric ceramic material has the general formula of Na 0.5 Bi 4.5-x (Li 1 / 3 Ce 2 / 3 ) x Ti4O 15, where the value of x is greater than 0 and less than or equal to 0.2, the structure is still a bismuth layered structure and retains the properties of the sodium bismuth orthotitanate matrix.
[0021] At the same time, due to Li + and Ce 4+ The ionic radius and Bi 3+ The ionic radius of the TiO6 octahedron is quite different, which can easily cause lattice distortion, making the inclination angle of the TiO6 octahedron along the a-axis larger and more sensitive to temperature changes. + and Ce 4+ Defect dipoles are formed, providing additional polarization changes when the temperature changes, making the pyroelectric ceramic material based on sodium bismuth titanate with a bismuth layered structure have a higher Curie temperature and a higher pyroelectric coefficient.
[0022] (2) When the preferred value of x in the present invention is 0.025 to 0.1, the relative dielectric constant of the polarized sodium bismuth titanate-based lead-free high-temperature pyroelectric ceramic is 100 to 150 under the test conditions of 25°C and 1 kHz room temperature, and the dielectric loss is less than 0.006. Compared with other existing sodium bismuth titanate-based materials or pyroelectric materials with bismuth layered structures, the pyroelectric coefficient is increased to 70 to 150 μCm due to the lattice distortion caused by the introduction of Li and Ce and the combined effect of the defect dipoles between Li and Ce. 2 K -1 ; Combined with the lower dielectric constant and dielectric loss value, the current response merit factor of pyroelectric is increased to (0.3~0.6)×10 -10 m V -1 , and the detectivity merit factor is increased to (1.6~4)×10 -5 Pa -1 / 2 , so that the NBT-based lead-free high-temperature pyroelectric ceramic of the present invention can withstand the high-temperature environment of reflow soldering without depolarization when used as the core component of the non-refrigerated pyroelectric red detector, so that it can adopt surface mount packaging technology to promote the miniaturization and integration of pyroelectric devices;
[0023] (3) The sodium bismuth titanate-based lead-free pyroelectric ceramic material with bismuth layer structure prepared by the present invention has a high Curie temperature and excellent pyroelectric performance. Figure 7 As shown, after high-temperature annealing, the pyroelectric performance of NBT-based high-temperature lead-free pyroelectric ceramics does not decay, has good stability, can be packaged using surface mount technology, and is suitable for chip pyroelectric devices.
[0024] In summary, the sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure provided by the present invention has the advantages of a higher Curie temperature, excellent pyroelectric properties and lower dielectric loss, and at the same time, the preparation process is simple and stable, the operation is convenient, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is an XRD test diagram of the sodium bismuth titanate-based lead-free pyroelectric ceramic with a bismuth layered structure illustrated in Example 1 of the present invention.
[0026] Figure 2 This is an XRD test diagram of the sodium bismuth titanate-based lead-free pyroelectric ceramic with a bismuth layered structure illustrated in Example 2 of the present invention.
[0027] Figure 3 This is an XRD test diagram of the sodium bismuth titanate-based lead-free pyroelectric ceramic with a bismuth layered structure illustrated in Example 3 of the present invention.
[0028] Figure 4 This is an XRD test diagram of the sodium bismuth titanate-based lead-free pyroelectric ceramic with a bismuth layered structure illustrated in Example 4 of the present invention.
[0029] Figure 5 This is an XRD test diagram of the sodium bismuth titanate-based lead-free pyroelectric ceramic illustrated in Comparative Example 1 of the present invention.
[0030] Figure 6 The data graph of the pyroelectric coefficient of the exemplary embodiment and the comparative example of the present invention as a function of temperature is shown.
[0031] Figure 7 The pyroelectric coefficients of the embodiments and comparative examples of the present invention at room temperature after heat treatment at different temperatures. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other. And the following NBT base is represented by a sodium bismuth titanate base with a bismuth layered structure.
[0033] Unless otherwise specified, the reagents used in the present invention are commercially available and of commercial grade and used as received. Standard experimental reagents and methods are used for the experimental tests involved in the present invention. The scientific and technical terms and abbreviations used in the present invention have the meanings commonly understood by those skilled in the art.
[0034] In the present disclosure, a sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure is prepared by steps of batching, primary ball milling, pre-sintering, secondary ball milling, granulation, molding, plastic removal, sintering, electrode preparation, polarization, etc. The following is an exemplary description of the preparation method of the sodium bismuth titanate-based lead-free pyroelectric ceramic with a bismuth layered structure provided by the present invention.
[0035] Ingredients: Commercially available, high-purity (purity of 98.00% or more, or purity of 99.00% or more) sodium carbonate (Na2CO3), bismuth trioxide (Bi2O3), titanium dioxide (TiO2), lithium carbonate (Li2CO3), cerium dioxide (CeO2) are mixed according to Na 0.5 Bi 4.5-x (Li 1 / 3 Ce 2 / 3 ) x Ti4O 15 The stoichiometric ratio is weighed and mixed to obtain powder.
[0036] Primary ball milling: The powders obtained above are mixed uniformly by ball milling, and anhydrous ethanol of the same mass as the powders is used as a solvent. The ball milling is performed for 6 to 24 hours, and zirconium dioxide balls are used for ball milling; after ball milling, the slurry is dried.
[0037] Pre-firing: transferring the dried slurry to an alumina crucible and pre-firing to obtain a pre-firing powder; wherein the pre-firing temperature is 600-900°C, the heating rate is not higher than 3-5°C / min, and the holding time is 1-5 hours.
[0038] Secondary ball milling: The pre-calcined powder is subjected to secondary ball milling and dried to obtain powder. The ball milling conditions are the same as those of the primary ball milling.
[0039] Granulation: Add a binder to the powder after secondary ball milling for granulation. For example, the binder is 5-10% of the mass of the powder, and the binder is 4-12wt% of PVA aqueous solution.
[0040] Molding: Put the granulated powder into the mold and press it with a pressure of 4 to 10 MPa to obtain a green embryo.
[0041] Plastic removal: Heat the raw embryo to 500-650℃ at a heating rate of 0.5-2℃ / min, keep it warm for 1-5 hours to remove organic matter.
[0042] Sintering: The green embryo after plastic removal is heated to 900-1200°C at a heating rate of 1-5°C / min, kept at this temperature for 1-5 hours, and cooled in the furnace to obtain sodium bismuth titanate-based lead-free pyroelectric ceramics with a bismuth layered structure.
[0043] Electrode preparation: Silver paste is applied to the upper and lower surfaces of the sodium bismuth titanate-based lead-free pyroelectric ceramic with a bismuth layered structure, and then kept at a high temperature of 500 to 700 degrees Celsius for 10 to 30 minutes.
[0044] Polarization: Place the sample in silicone oil and heat it to 150°C. Set the polarization electric field to 50 kV / cm, pressurize for 10 to 15 min, then increase the voltage to 80 kV / cm, maintain the voltage for 10 to 15 min, and finally increase the voltage to 100 kV / cm and keep the temperature for 10 to 15 min.
[0045] Specifically, the chemical composition of the sodium bismuth titanate-based lead-free pyroelectric ceramic with a bismuth layered structure of the present invention is: Na 0.5 Bi 4.5-x (Li 1 / 3 Ce 2 / 3 ) x Ti4O 15 , where x is greater than 0 and less than or equal to 0.2. Pyroelectric ceramics have the characteristics of high pyroelectric performance, low dielectric loss and high Curie temperature, and can be used in the field of uncooled infrared pyroelectric detection.
[0046] Preferably, the value of x is 0.025-0.1.
[0047] Preferably, the NBT-based lead-free pyroelectric ceramic material of the present invention has a relative dielectric constant of 100 to 150 under the test conditions of 25° C. and 1 kHz, and a dielectric loss of less than 0.006.
[0048] Preferably, the Curie temperature of the NBT-based lead-free pyroelectric ceramic material of the present invention is higher than 600°C, and the pyroelectric coefficient at room temperature is 70-150 μCm 2 K -1 The current response merit factor of pyroelectric is (0.3~0.6)×10 -10 m V -1 , voltage response merit factor is 0.02~0.05m 2 C -1 , the detectivity merit factor is (1.6~4)×10 -5 Pa -1 / 2 The pyroelectric performance of pyroelectric ceramics does not decay after annealing at 300°C.
[0049] The sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure of the present invention is further explained below through specific examples.
[0050] Embodiment 1:
[0051] Ingredients: High-purity Na2CO3, Bi2O3, TiO2, Li2CO3, CeO2 according to Na 0.5 Bi 4.475 (Li 1 / 3 Ce 2 / 3 ) 0.025 Ti4O 15 The stoichiometric ratio is weighed and mixed to obtain powder.
[0052] First ball milling: The powders obtained above are mixed evenly by ball milling, and anhydrous ethanol of the same mass as the powders is used as solvent, and the ball milling is performed for 6 hours, using zirconium dioxide balls. After ball milling, the slurry is dried.
[0053] Pre-sintering: The dried slurry is transferred to an alumina crucible and pre-sintered to obtain a pre-sintered powder. The pre-sintering temperature is 850°C, the heating rate is not higher than 5°C / min, and the holding time is 3 hours.
[0054] Secondary ball milling: The pre-calcined powder is subjected to secondary ball milling and dried to obtain powder. The ball milling conditions are the same as those of the primary ball milling.
[0055] Granulation: Add a binder to the powder after the secondary ball milling for granulation. The amount of the binder is 8% of the mass of the powder. The binder is an 8wt% polyvinyl alcohol solution.
[0056] Molding: Put the granulated powder into the mold and press it with a pressure of 4Mpa to obtain a green embryo.
[0057] Plastic removal: Heat the green embryo to 600℃ at a heating rate of 5℃ / min and keep it at this temperature for 2 hours to remove organic matter.
[0058] Sintering: The green embryo after plastic removal was heated to 1100°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain NBT-based lead-free pyroelectric ceramics.
[0059] Electrode preparation: Silver paste was coated on both the upper and lower surfaces of the NBT-based lead-free pyroelectric ceramic, and then kept at a high temperature of 600 degrees Celsius for 30 minutes.
[0060] Polarization: Place the sample in silicone oil and heat it to 150°C. Set the polarization electric field to 50 kV / cm, pressurize for 15 min, then increase the voltage to 80 kV / cm, maintain the voltage for 15 min, and finally increase the voltage to 100 kV / cm and maintain the voltage for 15 min.
[0061] The pyroelectric coefficient of the well-polarized pyroelectric ceramics is p = 77 μC m 2 K -1 . Pyroelectric current response figure of merit F i 0.32×10 -10 m V -1 , voltage response figure of merit F v 0.027×m 2 C -1 , detectivity merit factor F d 1.62×10 -5 Pa -1 / 2 .
[0062] Embodiment 2:
[0063] Ingredients: High-purity Na2CO3, Bi2O3, TiO2, Li2CO3, CeO2 according to Na 0.5 Bi 4.45 (Li 1 / 3 Ce 2 / 3 ) 0.05 Ti4O 15 The stoichiometric ratio is weighed and mixed to obtain powder.
[0064] First ball milling: The powders obtained above are mixed evenly by ball milling, and anhydrous ethanol of the same mass as the powders is used as solvent, and the ball milling is performed for 6 hours, using zirconium dioxide balls. After ball milling, the slurry is dried.
[0065] Pre-sintering: The dried slurry is transferred to an alumina crucible and pre-sintered to obtain a pre-sintered powder. The pre-sintering temperature is 850°C, the heating rate is not higher than 5°C / min, and the holding time is 3 hours.
[0066] Secondary ball milling: The pre-calcined powder is subjected to secondary ball milling and dried to obtain powder. The ball milling conditions are the same as those of the primary ball milling.
[0067] Granulation: Add a binder to the powder after the secondary ball milling for granulation. The amount of the binder is 8% of the mass of the powder. The binder is an 8wt% polyvinyl alcohol solution.
[0068] Molding: Put the granulated powder into the mold and press it with a pressure of 4Mpa to obtain a green embryo.
[0069] Plastic removal: Heat the green embryo to 600℃ at a heating rate of 5℃ / min and keep it at this temperature for 2 hours to remove organic matter.
[0070] Sintering: The green embryo after plastic removal was heated to 1100°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain NBT-based lead-free pyroelectric ceramics.
[0071] Electrode preparation: Silver paste was coated on both the upper and lower surfaces of the NBT-based lead-free pyroelectric ceramic, and then kept at a high temperature of 600 degrees Celsius for 30 minutes.
[0072] Polarization: Place the sample in silicone oil and heat it to 150°C. Set the polarization electric field to 50 kV / cm, pressurize for 15 min, then increase the voltage to 80 kV / cm, maintain the voltage for 15 min, and finally increase the voltage to 100 kV / cm and keep the voltage for 15 min.
[0073] The pyroelectric coefficient of the well-polarized pyroelectric ceramics is p = 103 μC m 2 K -1 . Pyroelectric current response figure of merit F i 0.43×10 -10m V -1 , voltage response figure of merit F v 0.036×m 2 C -1 , detectivity merit factor F d 2.39×10 -5 Pa -1 / 2 .
[0074] Embodiment 3:
[0075] Ingredients: High-purity Na2CO3, Bi2O3, TiO2, Li2CO3, CeO2 according to Na 0.5 Bi 4.5-0.075 (Li 1 / 3Ce 2 / 3 ) 0.075 Ti4O 15 The stoichiometric ratio is weighed and mixed to obtain powder.
[0076] First ball milling: The powders obtained above are mixed evenly by ball milling, and anhydrous ethanol of the same mass as the powders is used as solvent, and the ball milling is performed for 6 hours, using zirconium dioxide balls. After ball milling, the slurry is dried.
[0077] Pre-sintering: The dried slurry is transferred to an alumina crucible and pre-sintered to obtain a pre-sintered powder. The pre-sintering temperature is 850°C, the heating rate is not higher than 5°C / min, and the holding time is 3 hours.
[0078] Secondary ball milling: The pre-calcined powder is subjected to secondary ball milling and dried to obtain powder. The ball milling conditions are the same as those of the primary ball milling.
[0079] Granulation: Add a binder to the powder after the secondary ball milling for granulation. The amount of the binder is 8% of the mass of the powder. The binder is an 8wt% polyvinyl alcohol solution.
[0080] Molding: Put the granulated powder into the mold and press it with a pressure of 4Mpa to obtain a green embryo.
[0081] Plastic removal: Heat the green embryo to 600℃ at a heating rate of 5℃ / min and keep it at this temperature for 2 hours to remove organic matter.
[0082] Sintering: The green embryo after plastic removal was heated to 1100°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain NBT-based lead-free pyroelectric ceramics.
[0083] Electrode preparation: Silver paste was coated on both the upper and lower surfaces of the NBT-based lead-free pyroelectric ceramic, and then kept at a high temperature of 600 degrees Celsius for 30 minutes.
[0084] Polarization: Place the sample in silicone oil and heat it to 150°C. Set the polarization electric field to 50 kV / cm, pressurize for 15 min, then increase the voltage to 80 kV / cm, maintain the voltage for 15 min, and finally increase the voltage to 100 kV / cm and keep the temperature for 15 min.
[0085] The pyroelectric coefficient of the well-polarized pyroelectric ceramics is p = 142 μC m 2 K -1 . Pyroelectric current response figure of merit F i 0.59×10 -10 m V -1 , voltage response figure of merit F v 0.049×m 2 C -1 , detectivity merit factor F d is 3.47×10 -5 Pa -1 / 2 .
[0086] Embodiment 4:
[0087] Ingredients: High-purity Na2CO3, Bi2O3, TiO2, Li2CO3, CeO2 according to Na 0.5 Bi 4.5-0.1 (Li 1 / 3 Ce 2 / 3 ) 0.1 Ti4O 15 The stoichiometric ratio is weighed and mixed to obtain powder.
[0088] First ball milling: The powders obtained above are mixed evenly by ball milling, and anhydrous ethanol of the same mass as the powders is used as solvent, and the ball milling is performed for 6 hours, using zirconium dioxide balls. After ball milling, the slurry is dried.
[0089] Pre-sintering: The dried slurry is transferred to an alumina crucible and pre-sintered to obtain a pre-sintered powder. The pre-sintering temperature is 850°C, the heating rate is not higher than 5°C / min, and the holding time is 3 hours.
[0090] Secondary ball milling: The pre-calcined powder is subjected to secondary ball milling and dried to obtain powder. The ball milling conditions are the same as those of the primary ball milling.
[0091] Granulation: Add a binder to the powder after the secondary ball milling for granulation. The amount of the binder is 8% of the mass of the powder. The binder is an 8wt% polyvinyl alcohol solution.
[0092] Molding: Put the granulated powder into the mold and press it with a pressure of 4Mpa to obtain a green embryo.
[0093] Plastic removal: Heat the green embryo to 600℃ at a heating rate of 5℃ / min and keep it at this temperature for 2 hours to remove organic matter.
[0094] Sintering: The green embryo after plastic removal was heated to 1100°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain NBT-based lead-free pyroelectric ceramics.
[0095] Electrode preparation: Silver paste was coated on both the upper and lower surfaces of the NBT-based lead-free pyroelectric ceramic, and then kept at a high temperature of 600 degrees Celsius for 30 minutes.
[0096] Polarization: Place the sample in silicone oil and heat it to 150°C. Set the polarization electric field to 50 kV / cm, pressurize for 15 min, then increase the voltage to 80 kV / cm, maintain the voltage for 15 min, and finally increase the voltage to 100 kV / cm and keep the voltage for 15 min.
[0097] The pyroelectric coefficient of the well-polarized pyroelectric ceramics is p = 126 μC m 2 K -1 . Pyroelectric current response figure of merit F i 0.52×10 -10 m V -1 , voltage response figure of merit F v 0.045×m 2 C -1 , detectivity merit factor F d 2.23×10 -5 Pa -1 / 2 .
[0098] Comparative Example 1:
[0099] Ingredients: High-purity Na2CO3, Bi2O3, TiO2, Li2CO3, CeO2 according to Na 0.5 Bi 4.5 Ti4O 15 The stoichiometric ratio is weighed and mixed to obtain powder.
[0100] First ball milling: The powders obtained above are mixed evenly by ball milling, and anhydrous ethanol of the same mass as the powders is used as solvent, and the ball milling is performed for 6 hours, using zirconium dioxide balls. After ball milling, the slurry is dried.
[0101] Pre-sintering: The dried slurry is transferred to an alumina crucible and pre-sintered to obtain a pre-sintered powder. The pre-sintering temperature is 850°C, the heating rate is not higher than 5°C / min, and the holding time is 3 hours.
[0102] Secondary ball milling: The pre-calcined powder is subjected to secondary ball milling and dried to obtain powder. The ball milling conditions are the same as those of the primary ball milling.
[0103] Granulation: Add a binder to the powder after the secondary ball milling for granulation. The amount of the binder is 8% of the mass of the powder. The binder is an 8wt% polyvinyl alcohol solution.
[0104] Molding: Put the granulated powder into the mold and press it with a pressure of 4Mpa to obtain a green embryo.
[0105] Plastic removal: Heat the green embryo to 600℃ at a heating rate of 5℃ / min and keep it at this temperature for 2 hours to remove organic matter.
[0106] Sintering: The green embryo after plastic removal was heated to 1100°C at a heating rate of 3°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain NBT-based lead-free pyroelectric ceramics.
[0107] Electrode preparation: Silver paste was coated on both the upper and lower surfaces of the NBT-based lead-free pyroelectric ceramic, and then kept at a high temperature of 600 degrees Celsius for 30 minutes.
[0108] Polarization: Place the sample in silicone oil and heat it to 150°C. Set the polarization electric field to 50 kV / cm, pressurize for 15 min, then increase the voltage to 80 kV / cm, maintain the voltage for 15 min, and finally increase the voltage to 100 kV / cm and keep the voltage for 15 min.
[0109] For the test of pyroelectric ceramics with good polarization, the pyroelectric coefficient is p = 50μC m 2 K -1 . Pyroelectric current response figure of merit F i 0.21×10 -10 m V -1 , voltage response figure of merit F v 0.019×m 2 C -1 , detectivity merit factor F d 0.79×10 -5 Pa -1 / 2 .
[0110] Table 1 shows the pyroelectric performance parameters of the comparative examples and embodiments after polarization, which are as follows:
[0111]
[0112] Figures 1 to 5 The XRD patterns of the ceramic sheets prepared in Examples 1-4 and the comparative example are shown. It can be seen from the XRD patterns that all ceramic sheets have obvious (119) peaks, indicating that all of them are bismuth layered structures. In addition, the (200) / (020) peaks have different trends in different samples. In the comparative example, the peak separation is obvious. As the Li and Ce doping amounts increase, the peak separation gradually weakens, indicating that with the addition of Li and Ce, the crystal structure is significantly distorted.
[0113] Figure 6 The pyroelectric coefficient of Examples 1-4 and the comparative example varies with temperature. The pyroelectric coefficient of the comparative example at room temperature is 50 μC m 2 K -1 The pyroelectric coefficient of Example 3 is 142 μC m 2 K -1 . This shows that the present invention effectively improves the pyroelectric coefficient.
[0114] Figure 7 The pyroelectric coefficients of Examples 1-4 and the comparative example at room temperature after annealing at different temperatures are shown in Table 1. It can be shown that after annealing at 300°C, the pyroelectric coefficient does not decay, indicating that it can be packaged in the form of surface mounting by using the reflow soldering process.
[0115] Table 1 summarizes the pyroelectric coefficients and pyroelectric quality factor figures of merit of the embodiments 1-4 and the comparative example, indicating that the pyroelectric coefficients and figures of merit are all improved after doping LiCe in the present invention.
[0116] In summary, the present invention provides a sodium bismuth titanate-based lead-free pyroelectric ceramic with a bismuth layered structure, which introduces Li and Ce elements into the NBT matrix to produce lattice distortion, making it more sensitive to temperature changes. The pyroelectric performance is improved, and a good pyroelectric quality factor is obtained in combination with low dielectric loss. At the same time, it has an extremely high Curie temperature, which ensures that it does not depolarize during the reflow soldering process, which is conducive to the realization of surface mount packaging technology and the miniaturization and integration of devices.
[0117] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of protection of the present invention and its equivalent technology, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the scope of protection of the present invention.
Claims
1. A sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure, characterized in that: The chemical formula of the pyroelectric ceramic material is Na 0.5 Bi 4.5-x (Li 1 / 3 Ce 2 / 3 ) x Ti4O 15 , where the value of x is greater than 0 and less than or equal to 0.
2.
2. The sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure according to claim 1, characterized in that: The value of x is 0.025~0.
1.
3. The sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure according to claim 1, characterized in that: Under the test conditions of 25° C. and 1 kHz, the relative dielectric constant of the pyroelectric ceramic material is 100 to 150, and the dielectric loss is less than or equal to 0.
006.
4. The sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure according to claim 1, characterized in that: The pyroelectric ceramic material has a Curie temperature higher than 600°C and a pyroelectric coefficient of 70 to 150 μCm at 25°C. 2 K -1 The current response merit factor of pyroelectric is (0.3~0.6)×10 -10 m V -1 , voltage response merit factor is 0.02~0.05m 2 C -1 , the detectivity merit factor is (1.6~4)×10 -5 Pa -1 / 2 .
5. The method for preparing the sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) According to Na 0.5 Bi 4.5-x (Li 1 / 3 Ce 2 / 3 ) x Ti4O 15 According to the stoichiometric ratio, Na2CO3, Bi2O3, Li2CO3, CeO2 and TiO2 are weighed and mixed, ball milled once, and dried to obtain a mixed powder; (2) pre-sintering the mixed powder, performing secondary ball milling, drying, adding a binder and then granulating, molding, demolding and sintering to obtain a ceramic sheet; (3) coating both sides of the ceramic sheet with silver paste, sintering and shaping, placing the ceramic sheet in silicone oil for pressure polarization, and obtaining the sodium bismuth titanate-based lead-free pyroelectric ceramic material with the bismuth layered structure.
6. The method for preparing the sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure according to claim 5, characterized in that: The conditions of the first ball milling and the second ball milling are the same, specifically: using anhydrous ethanol as the solvent, setting the ball milling speed to 200-400 r / min, and ball milling for 6-24 hours.
7. The method for preparing the sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure according to claim 5, characterized in that: The pre-burning conditions are to heat up to 600-900°C at 3-5°C / min and keep warm for 1-5h; the plastic removal conditions are to heat up to 500-650°C at 0.5-2°C / min and keep warm for 1-5h; the sintering conditions are to heat up to 900-1200°C at 1-5°C / min and keep warm for 1-5h.
8. The method for preparing the sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure according to claim 5, characterized in that: The sintering and shaping conditions are to keep the temperature at 500-700° C. for 10-30 minutes.
9. The method for preparing the sodium bismuth titanate-based lead-free pyroelectric ceramic material with a bismuth layered structure according to claim 5, characterized in that: The polarization conditions are as follows: placing the sample in silicone oil and heating it to 150°C, setting the polarization electric field to 50 kV / cm, applying pressure for 10 to 15 minutes, then increasing the pressure to 80 kV / cm, maintaining the pressure for 10 to 15 minutes, and finally increasing the pressure to 100 kV / cm and maintaining the pressure for 10 to 15 minutes.
10. The method for preparing sodium bismuth titanate-based lead-free pyroelectric ceramic material with bismuth layered structure according to claim 5, characterized in that: The method further comprises: after the bismuth layered structure sodium bismuth titanate-based lead-free pyroelectric ceramic material is prepared, heat treatment is performed on it, specifically: the polarized bismuth layered structure sodium bismuth titanate-based lead-free pyroelectric ceramic material is placed in an annealing furnace at 300° C., kept warm for 5 to 15 minutes, and then taken out and cooled naturally.
Citation Information
Patent Citations
Unleaded piezoelectric ceramic consisting of B-site composite Bi-based compound and preparation method thereof
CN102320828A
Leadless piezoelectric ceramic composed of B-bit composite Bi-based compound and preparation method thereof
CN103159475A
Leadless piezoelectric ceramic and preparation method thereof
CN107382316A
Nonvolatile semiconductor storage device
JP1994097455A
Bismuth layered structural ferroelectric crystal, its producing method, and electronic device using the same
JP2005213066A